Wokół soboru nicejskiego (325): na kanwie monografii autorstwa Henryka Pietrasa SJ - Bralewski, Sławomir (Vox Patrum, 2016)
The Council convened by emperor Constantine the Great to Nicea in the year 325 still arouses keen interest of researchers around the world. Against the background of international scholarship, the achievements of Polish academics look quite modest. That is why one should especially appreciate the publication of a book (written in Polish) on the subject by Henryk Pietras, an acclaimed Polish patrologist. The monograph is noteworthy for a number of reasons and compels the reader to a thorough reflection on a cornucopia of facts that have been already discussed by numerous academics and subject to manifold interpretations. Its special merit lies first and foremost in an erudite analysis of sources conducted by the Author, which is competent enough to exhort all the interested to (at least) re-think their views. It is necessary to admit that the Academic is right, when he argues that the Council (firstly convened to Ancyra, and subsequently to Nicea) was not organized for the reason of discussing the Arian controversy. In reality, it seems that the primary reason for the meeting was the Donatist schism, which the Patrologist underestimated, and additionally the problem of reaching an agreement on a date of the Passover celebration. Certainly, the Council was not of an anti-Arian nature, but Arius was condemned by the ecclesiastic meeting as the one who rejected a laboriously reached compromise as for the form of the credo and renounced the term homoousios.